2014
DOI: 10.3171/2014.6.spine13523
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of the impact of various facet joint lesions on the primary stability of anterior plate fixation in cervical dislocation injuries: a cadaver study

Abstract: Object Injuries of the subaxial cervical spine including facet joints and posterior ligaments are common. Potential surgical treatments consist of anterior, posterior, or anterior-posterior fixation. Because each approach has its advantages and disadvantages, the best treatment is debated. This biomechanical cadaver study compared the effect of different facet joint injuries on primary stability following anterior plate fixation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…The C4/C5 segment from this model was extracted and analyzed. The reason for choosing the C4/C5 motion segment involved that the large amount of facet injuries commonly occurred on this joint in clinical practice, its use in previous cervical spine models, and its similarity to other segments in the full spine model [ 15 , 16 ]. Our previous study have showed validation of the C4/C5 FE model in detail by comparing with the experimental data obtained from normal cadaver and published data reported in the literatures [ 12 , 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The C4/C5 segment from this model was extracted and analyzed. The reason for choosing the C4/C5 motion segment involved that the large amount of facet injuries commonly occurred on this joint in clinical practice, its use in previous cervical spine models, and its similarity to other segments in the full spine model [ 15 , 16 ]. Our previous study have showed validation of the C4/C5 FE model in detail by comparing with the experimental data obtained from normal cadaver and published data reported in the literatures [ 12 , 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Trotz alledem gilt es, im Falle einer traumatisch bedingten Instabilität im subaxialen Bereich diese Verletzungen zu detektieren, bei denen primär das dorsale Vorgehen indiziert ist [14]. Hier handelt es sich um Verletzungen vom Typ C oder B mit Luxationen der kleinen Wirbelgelenke, bei denen eine ventrale Reposition nicht möglich ist oder von dorsal primär eine Dekompression erforderlich wird (▶ Abb.…”
Section: Indikationen Zur Dorsalen Stabilisierung Der Oberen Hwsunclassified
“…Loss of postoperative alignment occurred in 13% of subjects. In a biomechanical cadaver study, Oberkircher et al . compared the effect of different facet joint injuries on primary stability following anterior plate fixation.…”
Section: Introductionmentioning
confidence: 99%